An Economic Analysis of the Impact of Oil Prices on Urban Structures - Melvin, James R. (Heritage., 1983)
This study examines ways in which residents of Canadian cities are affected by increases in petroleum prices. The authors apply economic models of residential and industrial location to determine the response of individuals and firms to higher oil prices in the short run and the long run.